PENGARUH TOTAL ASSETS TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET UNTUK INDUSTRI PROPERTI DI BURSA EFEK INDONESIA PERIODE 2019 - Mohamad Makrus (LPPM STIE PERTIBA Pangkalpinang, 2021)
In general, the company's activities aim to optimize profitability in a period and the end is the prosperity of the company owners or shareholders (stockholders). The increase or decrease in the prosperity of shareholders can be seen from financial ratios, one of which is the return on assets in each period. This study aims to determine and analyze the effect of total assets turnover and debt to equity ratio on return on assets for the property industry on the Indonesian stock exchange for the period 2019. This type of research is quantitative by conducting hypothesis testing, to test the effect of a number of variables designed in the equation model. The type of data used in this study is secondary data sourced from the Indonesian stock exchange for the 2019 period. The research data were analyzed using a cross-sectional data regression analysis technique whose processing was done through SPSS version 25 software. The results show that there is a simultaneous and partial significant effect of total assets turnover and debt to equity ratio on return on assets for the property industry on the Indonesian stock exchange for the 2019 period. Partially, total assets turnover has a positive and significant effect on return on assets, while the debt to equity ratio has a negative and significant effect on return on assets for the property industry on the Indonesian stock exchange for the period 2019.